Comparison between Original and Modified Intracerebral Hemorrhage Scores in Spontaneous Intracerebral Hematoma in Predicting Outcome in a Tertiary Care Center in Nepal - Sah, Hemant Kumar; Shrestha, Dipendra; Phuyal, Suman; Pradhanang, Amit Bahadur; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2026)
Introduction: Spontaneous intracranial hemorrhage is the presence of a parenchymal bleed in the absence of trauma or surgery in brain. The original Intracerebral hemorrhage score utilizes the cut-off age of 80 years, whereas the modified Intracerebral hemorrhage score used a lower cut-off age which may better prognosticate the outcome of Intracerebral hemorrhage in the populations with shorter life expectancy. The primary objective of this study was to compare the original with modified intracerebral hemorrhage scores in predicting mortality in Nepalese population with intracerebral hemorrhage.Materials and Methods: Patients ≥16 years, with spontaneous Intracerebral hemorrhage, who were admitted in Tribhuvan University Teaching Hospital in the Department of Neurosurgery and Neurology between 15th March, 2019 and 30th November, 2019, were included in the study. Original and modified Intracerebral hemorrhage scores were recorded separately at the time of admission. The outcome was measured using the modified Rankin Scale at 6 months. To compare the predictive ability of original and modified Intracerebral hemorrhage for mortality and outcome, receiver-operating characteristics curves were compared; and areas under the curve was calculated. DeLong’s test was used to compare the area under the Receiver Operating Characteristic. Sensitivity and specificity were calculated for the diagnostic accuracy; and were plotted in Receiver Operating Characteristic. Youden's index was calculated to determine the discrimination ability of both scores.Result: A total of 89 patients were enrolled in the study. Only thirteen patients (14.6%) were ≥80 years. The 30-day and 6-month mortality was 24.7% and 33.7% respectively. Hosmer-Lemeshow test showed a good model fit for both the scores for mortality and good outcome at 6 months.Conclusion: Prediction of 30-day mortality by modified intracerebral hemorrhage score is similar to the original intracerebral hemorrhage score. However, there was a slight trend of better prediction for good outcome at 6 months, using the modified score.